The health professionals’ perception related to the importance of the dental surgeon in the Intensive Care Unit - Bruna Lopes SILVEIRA; Dayse Layanne Pereira MENESES; Eduardo Souza de Lobão VERAS; José Pereira de Melo MELO NETO; Luana Kelle Batista MOURA; Maria Soraya Alves Evangelista MELO (RGO: Revista Gaúcha de Odontologia, 2020)
ABSTRACT Objective To evaluate the perception of ICU professionals about the importance of the dental surgeon in the Intensive Care Unit. Method Descriptive research, quantitative-qualitative approach. The participants were 22 people, aged 22 years and older who work in the ICUs of private hospitals in the city of Teresina-PI. The data were produced through in-depth interviews in a reserved room of the unit from March 01 to 22, 2018. A semi-structured instrument was divided in two parts: characterization of the participants and open and closed questions on the theme. The data were processed with IRAMUTEC software support and analyzed by means of the Hierar-chical Descending Classification. The research was approved by an Ethics and Re-search Committee with the opinion number 2516806. Results 22 units of elementary texts were identified, from 68 text segments. A total of 2337 occurrences were rec-orded, using 75% of the total corpus. The results are presented in two axes: Axis 1 - Diagnosis and installation measures of control of the oral infections in the ICU, di-vided into three classes: class 4, 5, 1. Axis 2 - Conceptual aspects about infections in ICUs linked to the importance of CD, was divided into three classes: Class 2.3, 6. Conclusion The study concluded that the professionals emphasize the importance of CD in the multidisciplinary team of ICUs to ensure comprehensive and comprehensive treatment of the patient, promoting the possibility of an accurate diagnosis, ad-equate prevention, prognosis and improvement in the quality of life of these individuals.